HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP TENTANG HIGIENE SANITASI PETUGAS PENJAMAH MAKANAN DENGAN PRAKTEK HIGIENE SANITASI DI UNIT INSTALASI GIZI RSJ DR AMINO GONDOHUTOMO SEMARANG 2OO8 - Meikawati W; Astuti R; Susilowati - (Universitas Muhammadiyah Semarang, 2010)
Background: Food ltygiene and sanitation is practice lheory about knowledge, atlitude and human behavior in adhering health, cleanliness and safety principal in handling food In Jood ionrgr*rn at hospital saiirafionfood process involved manyfactors like source of food-stuff'procising unlill become food, serving to customer and many other environmental factors. Objectivi: To know ti correlarion between knowledge and attitude offood taster fficer with pr*tig of ttygiene andfood sanitation in nutrition unit Dr. Amino Gondohutomo mental hospitol Semarang 2008.Method:-The used method in this research is survey wilh Cross Sectional approach. Population are 20 subject. Independent variable ore knowledge and attitude offoodtaster officer hygiene and food sanitLtion ani dependent variable is practice ol hygiene andJood sanitation- Data analized by Rank Spearman. Result : hesult of research obtained data of the most subiect age j6-45 are 16 people (80'0%') The longest time of workbetween It-20years are l2 people (60,0%o)The highest of academyare a peopie (40,0%ri There are 9 people (45,0o/o) follov'ed training about food sanitation and trygieie. Half of subject have good knowledge and attitude to hygiene efort andfood sanitationii tO propi, (SO,O,lol.freaoiinantly (75%o) subiecr having good category ofpractice.%o). Result of Raik Spror*on cotelalion test shown that there is no significanl correlation between knowledge'with hygiene practice andfood sanitation. There is significant correlation between attitudeiith hyg;ene practice andfood sanitation and positive linear pallern.Conclusion: There is no correlation between knotiledge v,ilh hygiene practice andfood sanitation (p value – 0,655). There is correlatiott beht,een attitude with hygiene practice andfood sanitation (p value :0,017).Keyword : knowledge, attitude' practice offood sanitation and hygiene'